2010
DOI: 10.1111/j.1469-8137.2010.03377.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of chlorophyll catabolites photosensitizes the hypersensitive response elicited by Pseudomonas syringae in Arabidopsis

Abstract: Mur, L. A. J., Aubry, S., Mondhe, M., Kingston-Smith, A. H., Gallagher, J. A., Timms-Taravella, E., James, C. L., Papp, I., Hortensteiner, S., Thomas, Howard, Ougham, H. J. (2010). Accumulation of chlorophyll catabolites photosensitizes the hypersensitive response elicited by Pseudomonas syringae in Arabidopsis. ? New Phytologist, 188 (1), 161-174. IMPF: 06.51 Sponsorship: Biotechnology and Biological Sciences Research Council (BBSRC)The staygreen (SGR) gene encodes a chloroplast-targeted protein which promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
104
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 85 publications
9
104
0
1
Order By: Relevance
“…In line with this is the fact that all SGR mutants analyzed so far, retain high levels of LHCII subunits (Aubry et al 2008;Jiang et al 2007) and a role of SGR in destabilizing Chl-binding protein complexes as a prerequisite for the subsequent degradation of apoproteins and Chl has been suggested (Park et al 2007;Hörtensteiner 2009). In Arabidopsis, levels of SGR were shown to positively correlate with the extent of development of disease or hypersensitive response symptoms during Pseudomonas syringae infections (Mur et al 2010;Mecey et al 2011) and phototoxic Pheide a was considered to contribute to cell death execution (Mur et al 2010). These results are in agreement with the light dependency shown for several plant-pathogen interactions and indicate a link between plant responses to pathogen infections and Chl breakdown.…”
Section: The Stay-green Proteinmentioning
confidence: 99%
“…In line with this is the fact that all SGR mutants analyzed so far, retain high levels of LHCII subunits (Aubry et al 2008;Jiang et al 2007) and a role of SGR in destabilizing Chl-binding protein complexes as a prerequisite for the subsequent degradation of apoproteins and Chl has been suggested (Park et al 2007;Hörtensteiner 2009). In Arabidopsis, levels of SGR were shown to positively correlate with the extent of development of disease or hypersensitive response symptoms during Pseudomonas syringae infections (Mur et al 2010;Mecey et al 2011) and phototoxic Pheide a was considered to contribute to cell death execution (Mur et al 2010). These results are in agreement with the light dependency shown for several plant-pathogen interactions and indicate a link between plant responses to pathogen infections and Chl breakdown.…”
Section: The Stay-green Proteinmentioning
confidence: 99%
“…The lines represent linear adjustment at a probability level P<0.05 photosynthesis (Chou et al 2000). Mur et al (2010) showed that reactive oxygen species caused chlorophyll degradation in the course of Pseudomonas syringae infection and that light-excited products of chlorophyll degradation, e.g., pheophorbide a (Pheide) may be an additional source of ROS. It was suggested in several other studies that pheophorbide a can act as a photosensitizer that generates ROS in response to light (Tanaka et al 2003;Hörtensteiner 2004;Pruzinska et al 2005;Tanaka and Tanaka 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work we described the changes in the activity of the photosynthetic apparatus and chlorophyll content in the cotyledons of winter rape growing on an agar medium containing a toxic culture of L. maculans / L. biglobosa filtrates (Hura et al 2014b, c). Reactive oxygen species are claimed to be the main cause of chlorophyll degradation, and this is in turn one of the symptoms of progressive cell death (Mur et al 2010). It is well known that chlorophyll level is crucial for the activity of the photosynthetic apparatus, and hence, indirectly, for the level of carbohydrates (primary metabolites) that are the basis for the synthesis of secondary metabolites (including phenolic compounds), influencing the plantfungal pathogen interaction (Hura et al 2014d).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] It is reasonable to envisage that damage of the membrane integrity of these two organelles reflects the effects of vast amounts of ROS produced by the electron transport chains. 25,26 Recent evidence supports the destruction of the photosynthetic apparatus associated to the generation of ROS in the HR. 26 At this time of PCD progression, ROS could be contributing to shut down the energy machinery in the cell, which ultimately would become the point of no-return of PCD 27 as part of the execution program of the cell death mediated by LCBs.…”
mentioning
confidence: 99%
“…25,26 Recent evidence supports the destruction of the photosynthetic apparatus associated to the generation of ROS in the HR. 26 At this time of PCD progression, ROS could be contributing to shut down the energy machinery in the cell, which ultimately would become the point of no-return of PCD 27 as part of the execution program of the cell death mediated by LCBs.…”
mentioning
confidence: 99%